2020
DOI: 10.1088/1361-6455/ab7e1c
|View full text |Cite
|
Sign up to set email alerts
|

The 5d → 6p EUV photoabsorption spectra of Pb II and Bi III: evidence of excited states

Abstract: We have measured the photoabsorption spectra of Pb II and Bi III in the wavelength range between 37 and 70 nm. A number of features in the spectra have been identified with the aid of the Cowan suite of atomic codes. 5d → 6p transitions from the ground configuration (5d106s26p) and three excited configurations (5d106s26d, 5d106s27s, 5d106s6p2) give rise to the most prominent features in the measured spectra. Evidence of excited states including (5d106s6p2 (4P3/2, 4D3/2)) for Pb II and (5d106s6p2 (4P1/2, 4P3/2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…Note that the experimentally observed the excitation thresholds of the lines, namely E 182.2 ≈ 8.55 eV and E 143.4 ≈ 8.65 eV, correspond to the excitation of the 6d 2 D 5/2 and 6d 2 D 3/2 levels from the ground 6s 2 6p 2 P o 1/2 level. The observed structure can be explained by the population of the 6d 2 D 3/2 and 6d 2 D 5/2 resonance levels due to both electron decay of the atomic autoionizing states (AIS) [27][28][29][30][31][32] and radiative transitions from the higher ionic levels and AIS of the Pb + ion [33]. Thus, the first three maxima in the energy range from the thresholds up to the Pb + ion ionization potential (15.03 eV) are related, most likely, to the electron decay of the Pb atom 5d 10 6s6p 2 np (n ≥ 7) AIS [27,28] as well as the radiative transitions from the ionic 5d 10 6s 2 np, m f (n ≥ 7, m ≥ 5) levels [33].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Note that the experimentally observed the excitation thresholds of the lines, namely E 182.2 ≈ 8.55 eV and E 143.4 ≈ 8.65 eV, correspond to the excitation of the 6d 2 D 5/2 and 6d 2 D 3/2 levels from the ground 6s 2 6p 2 P o 1/2 level. The observed structure can be explained by the population of the 6d 2 D 3/2 and 6d 2 D 5/2 resonance levels due to both electron decay of the atomic autoionizing states (AIS) [27][28][29][30][31][32] and radiative transitions from the higher ionic levels and AIS of the Pb + ion [33]. Thus, the first three maxima in the energy range from the thresholds up to the Pb + ion ionization potential (15.03 eV) are related, most likely, to the electron decay of the Pb atom 5d 10 6s6p 2 np (n ≥ 7) AIS [27,28] as well as the radiative transitions from the ionic 5d 10 6s 2 np, m f (n ≥ 7, m ≥ 5) levels [33].…”
Section: Figurementioning
confidence: 99%
“…In addition, starting from the energy ≈ 11 eV the 5d 9 6s 2 6p 3 atomic AIS [27,28] also make a contribution to these maxima. The structure observed above the Pb + ion ionization potential can be related to the electron decay of the atomic 5d 9 6s 2 6p 2 np, m f (n ≥ 6, m ≥ 5) AIS [27,28] as well as the ionic 5d 9 6s 2 6pnp, m f (n ≥ 7, m ≥ 5) and 5d 10 6p 2 nd, mp (n ≥ 6, m ≥ 7) AIS [29][30][31][32]. Note that the 5d 10 6s6p 2 np, 5d 9 6s 2 6p 2 np, m f , and 5d 9 6s 2 6p 3 atomic AIS are formed due to the incident electron resonance capture with simultaneous excitation of one of the electrons of the Pb + ion (Equation ( 4)).…”
Section: Figurementioning
confidence: 99%
“…Using the DLP technique, 5d photoabsorption in Pb 2+ and Bi 3+ was observed between 33 and 60 eV, identifying over 30 new transitions and resulting in an improved value for the ionisation potential of Bi 2+ [12]. This work was expanded to Pb + and Bi 2+ in the range 17.7-33.5 eV, where 5d → 6p transitions from the ground-and three low lying excitedconfigurations were included to explain the observed spectra [13]. A detailed photoabsorption study of laser-produced gold plasmas identified 5p → 5d, 6s, and 4f → 5d, 6d transitions in the ions Au 2+ , Au 3+ , and Au 4+ in the 70-120 eV region [3].…”
Section: Introductionmentioning
confidence: 99%
“…We were very interested to read the comments made [1] in relation to the above paper [2] which we recently published in J. Phys. B: At.…”
mentioning
confidence: 99%
“…We can write authoritatively only on the spectrum that we have acquired with our experimental setup and compare that with our calculations and those presented in the comment. We show our Bi 2+ spectrum (figure 1(a)) [2] along with the same spectrum compared with the atomic line data (broadened by our instrumental width) extracted from table 1 in [1] (cf figure 1(b) below). It is clear that the computed spectral distribution in figure 1(b) does not match well to our observed distribution with respect to relative line strengths, albeit the wavelengths match quite well to some of the prominent features.…”
mentioning
confidence: 99%